A case of disseminated tuberculosis during a twin pregnancy following in vitro fertilization. (July 2022) - Kestens, L; Van Acker, L; Hoorens, A; Kreps, E O; Haerynck, F; Debrock, A; Catry, V; Weyers, S; Roelens, K; Van Braeckel, E
Highlights (for review): - A woman was diagnosed with miliary tuberculosis following a 13th IVF procedure. - Underlying pelvic TB was suspected, probably the overlooked cause of her infertility. - Pregnancy and the postpartum are risk factors for a complicated disease course. Abstract: A woman presented with cough, fever, and dyspnea during a twin pregnancy following a 13th in vitro fertilization procedure. Ultimately, she was diagnosed with miliary tuberculosis and tuberculostatic treatment was initiated, complicated by drug-induced hepatotoxicity. In retrospect, previous pelvic tuberculosis had likely been overlooked. This case report highlights the need to recognize tuberculosis as a cause of infertility even in low-incidence countries and emphasizes that the peripartum period is a major risk factor for drug-induced liver injury.